2000
DOI: 10.1385/ijgc:28:2:091
|View full text |Cite
|
Sign up to set email alerts
|

Does Mortality Occur Early or Late in Acute Pancreatitis?

Abstract: Approximately half of deaths in acute pancreatitis occur within the first 14 d owing to organ failure and the remainder of deaths occur later because of complications associated with necrotizing pancreatitis. Improvement in mortality in the future will require innovative approaches to counteract early organ failure and late complications of necrotizing pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 27 publications
1
55
0
5
Order By: Relevance
“…Wilson et al [17] analyzed 126 deaths from acute pancreatitis; the time to fatal outcome was <7 days in the majority of the patients. In the report by Mutinga et al [6], nearly 50% of the deaths occurred within the first 2 weeks. In contrast, a review of 263 acute pancreatitis cases by Gloor et al [4] found no patients dying within the first 2 weeks after onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson et al [17] analyzed 126 deaths from acute pancreatitis; the time to fatal outcome was <7 days in the majority of the patients. In the report by Mutinga et al [6], nearly 50% of the deaths occurred within the first 2 weeks. In contrast, a review of 263 acute pancreatitis cases by Gloor et al [4] found no patients dying within the first 2 weeks after onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It had been suggested that the occurrence of early deaths resulting from multiple organ dysfunction syndrome (MODS) decreased with advanced intensive care [4]. Nevertheless, other studies described that over half of the deaths occurred early and were primarily due to MODS rather than due to infection [5, 6]. Accordingly, it still remains unknown whether the majority of deaths occur early or late.…”
Section: Introductionmentioning
confidence: 99%
“…Although older literature suggested that 80% of deaths occur after several weeks of illness as a result of infected necrosis, more recent surveys have shown considerable variation with several reports showing a reasonably even distribution of early deaths (within 1-2 wk) versus later deaths (46,72,76,150,151,163), a few showing the majority of deaths within the first 2 wk (67,75), and others showing the majority of deaths after the first 2 wk (59,89,135). These variations reflect a variety of influences including percentage of very ill patients referred to a reporting hospital compared to patients admitted directly.…”
Section: Overview Of Acute Pancreatitismentioning
confidence: 99%
“…16 Geralmente, ocorre devido à síndrome da resposta inflamatória sistêmica e falência orgânica nas primeiras duas semanas e, após esse período, costuma ser decorrente de sepse e suas complicações. 19 O cistoadenoma mucinoso pancreático neoplásico é sugerido após a aferição do marcador tumoral antígeno carcinoembriogênico (CEA) colhido por punção. Valores acima de 110 ng/mL têm sensibilidade de 81% e especificidade de 98% no diagnóstico.…”
Section: Evoluçãounclassified